Age based evaluation of nut aspiration risk - Jill N. D’Souza; Taher S. Valika; Bharat Bhushan; Jonathan B. Ida (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To identify an age at which initiation of whole nut into the pediatric diet could be considered safe, by evaluating the age distribution of children undergoing bronchoscopy with removal of nut or seed material from the airway. Method A retrospective chart review over a ten-year period identifying children age 0–18 that have undergone bronchoscopy with retrieval of airway foreign bodies. A statistical analysis of demographic data was carried out to identify age distribution of aspiration events. Results Sixty-four cases of foreign body aspiration were identified, of which 43 (67%) were of organic origin, specifically nuts. A Fisher’s exact test was carried out on the cumulative percentage of organic foreign body aspirations to identify the age distribution of nut aspiration events. A statistically significant decrease in organic foreign body aspirations occurred at approximately 36 months of age (p = 0.004). Conclusion Foreign body aspiration is a leading cause of accidental injury or death in children. Nut and other small organic foreign bodies account for a significant portion of accidental aspiration events, however, no guidelines exist regarding appropriate age of whole nut introduction into the diet. Our study suggests that 90% of pediatric nut aspiration events occur under the age of 36 months. We suggest supervised introduction of whole nuts between the ages of 3 and 4 years. Official guidelines regarding this should be considered by professional pediatric societies. Level of evidence 4